Effects of Electroacupuncture to the Trigeminal Nerve Area on the Autonomic Nervous System and Cerebral Blood Flow in the Prefrontal Cortex. Issue 5 (October 2017) - Waki, Hideaki; Suzuki, Takuya; Tanaka, Yuki; Tamai, Hideaki; Minakawa, Yoichi; Miyazaki, Shogo; Yoshida, Naruto; Uebaba, Kazuo; Imai, Kenji; Hisajima, Tatsuya
Background: The autonomic nervous system and trigeminal nerve are involved in adjusting flow through diverging cerebral arteries in the prefrontal cortex. The purpose of this study was to examine the effect of 100 Hz electroacupuncture (EA) to the trigeminal nerve area on cerebral blood flow and autonomic nervous system function. Method: This was a randomised crossover study of 16 healthy volunteers who were assigned to an EA or control group. Stimulation (in the EA group) was performed five times, each after 1 min of rest. Needles were inserted at the inner edge of the eyebrows and 1 cm from the front hairline midpoint. We used high-frequency (HF) and low-frequency (LF) components of heart rate (HR) variability to assess autonomic nervous system function. HF and LF/HF ratio were taken as indicators of parasympathetic and sympathetic nervous system activity, respectively. We measured cerebral blood flow using a two-channel near-infrared spectroscope. Results: In the EA group, HR significantly decreased (p=0.004) and HF significantly increased (p=0.006) relative to baseline. By contrast, there were no significant changes in HR or HF within the control group (p>0.05). Accordingly, HR tended to be lower (p=0.087) and HF greater (p=0.071) in the EA group versus the control group. There were no significant differences in LF/HF ratio within/between groups. Compared with the control group, cerebral blood flow was significantly greater in the left (p=0.048) and right (p=0.016) prefrontal cortex in the EA group. Conclusions: Delivery of 100 Hz EA to the trigeminal nerve area reduces HR and increases parasympathetic nervous activity and cerebral blood flow.